Understanding Inadequate Response to First Grade Multi-Tier Intervention: Nomothetic and Idiographic Perspectives - Greulich, Luana (Learn Disabil Q, 2014)
The purpose of this study was to use a mixed methods approach to learn about inadequate response to a year-long multi-tier RTI model that allowed first-grade students to move up and down tiers. Participants were 156 students who received supplemental intervention services during a larger multi-tier RTI study involving classrooms and 522 students across 10 schools. Findings from an all-subset regression indicate letter word reading, the fluency composite, and blending words explained the most variance (15%) in response among initial skills. Adding additional teacher ratings of behavior and academics, accounted for a small amount of additional variance (3%) in group membership. The ROC curve analysis indicated 87.5% of students were correctly classified, yielding a sensitivity of 85.3 and a specificity of 65.0. Findings from qualitative observations of intervention sessions suggest inadequate responders demonstrated physical and verbal task avoidance and displayed emotions of hopelessness and shame. Implications for practice are discussed.